Design of a Web-Based Inventory Management System For Toko Fajar Mandiri Tani In Karangmulya, Suradadi - Maulidi, Muhammad Akwan; Aries Setyani Wahyu Prasetyawati (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This study addresses the problem of mismatched stock records and actual inventory levels in the warehouse of Toko Fajar Mandiri Tani, which often disrupts operations and customer service. To solve this, the study used data collection methods such as direct observations, interviews with staff, and literature review to build a strong foundation for the system design. The analysis of the current manual system identified its strengths and weaknesses, which became the basis for developing a new solution. The result is a web-based inventory management system that helps record, monitor, and report stock levels in real-time. The system implementation showed significant benefits, including improved accuracy in inventory data, reduced risks of overstocking or understocking, and better stock order recommendations. Additionally, the automated inventory reporting feature supports faster and more informed decision-making. This system not only records stock but also streamlines the overall operational management of the store. The findings of this study offer a practical technological solution to help small and medium-sized businesses manage their inventory effectively.